(untitled) (INNOVATIVE ECONOMY, 2020)
Tymoschenko M.M. ECONOMIC MECHANISM FOR THE IMPLEMENTATION OF THE STRATEGY OF SUSTAINABLE RURAL DEVELOPMENT UNDER THE CONDITIONS OF STABILITY: METHODS AND INSTRUMENTS Purpose. The paper deals with the deepening of scientific and methodological provisions and substantiation of practical recommendations for the development of organizational and economic mechanism for implementation of the strategy of sustainable development of rural areas of Ukraine. Methodology of research. The theoretical and methodological basis of the research is the dialectic, systemic and synergetic scientific approaches. In the process of research, the following special scientific methods have been used: abstract cand logical, in particular methods of induction and deduction, analogy and comparison, operationalization of concepts; method of theoretical generalization and analysis and synthesis; various methods of economic and statistical methods (statistical observation, comparison, tabular, graphic). Findings. It should be emphasized that theoretical and methodical principles of forming an economic mechanism for realization of the strategy of sustainable rural development of Ukraine are discussed. It is determined that the only way of implementing the strategy of the stability of rural development is to establish an economic mechanism that includes methods and tools that will provide a certain type of balance between the social, economic and environmental components of the rural population. It has been established that the basis of sustainable rural development should be the effective means, levers and actions of both economic and organizational and managerial character, which will affect the interests of the economic structures in the village (agricultural institutes of different forms of ownership and types of management, farms and rural households) and will promote not only the intensification of economic life in the countryside, but also the achievement of social well-being and the solution of a number of environmental problems. Originality. It is proved that the economic mechanism of implementation of the strategy of sustainable development of rural territories of Ukraine, in contrast to the existing approaches, should be considered as a multifunctional system of political, legal, methodological, socio-economic, organizational-industrial, environmental protection, innovation-investment and other measures. That are aimed to provide real progressive changes in the productive, social and environmental spheres of the countryside for improving the well-being and quality of life of the rural population and maintaining you are in general. Practical value. The obtained results, the formulated conclusions and proposals will contribute to solving theoretical and practical problems of forming an effective economic mechanism for implementing the strategy of sustainable socio-economic development of rural territories as a key element of the modern model of the rural economy of Ukraine. Key words: rural areas; economic mechanism; sustainable rural development; socio-economic problems; strategy; methods; levers; tools.